Implementación de una metodología de mejora de calidad y productividad en una pyme del sector plástico - Buestán Ormaza, Byron Xavier (2010)
In Ecuador, there are few companies which include in their daily activities, some kind of methodology to improve and keep quality and productivity. In this ocassion, from PYMEs: Small and Medium Businesses of Ecuador (by its abbreviation in Spanish), GRUPO INDUSTRIAL PLASTIGRUP was chosen and it shows organizational issues, high levels of damage products, lack of quality control system and deficiency of interdepartmental communication. In order to solve these problems, some methods were applied to reach the main objective which is the improvement of quality and productiviy levels in the company. In order to achieve the proposed goal, some steps were necessary to be taken such as: 1) Job organization by the implementation of 5S Japanese Method and Visual Control, 2) Better approach to the customer expectations by the Expectations Map and Job Map techniques, 3) Interdepartamental communication mecanisms were improved and 4) a quality improvement process started by the application of Quality Statistical Control, Seven Basic Control tools and seven waste tools.